Lattice-Boltzmann Method with immersed boundary conditions for fluid simulations of multiples species - Boroni, Gustavo Adolfo (2013)
An algorithm to simulate multiples mixtures in single phase with different molecular weights is presented. The coupling of multiple mixtures with the immerse boundary method is proposed. This algorithm is designed to model problems of multiple mixtures using Lattice Boltzmann method which in turn can interact with complex objects modeled with immersed boundaries. The Lattice Boltzmann method is derived from kinetic theory by discretizing multiples fluid Boltzmann equations in which cross-collisions and self-collisions are treated independently. The method is validated against analytical solution in diffusion of binary mixtures and evaluated in ternary mixtures in a curved channel.